Tehnici auctoriale de încriptare a simbolului infantil. Studiu de caz: Jean-Jacques Rousseau, Émile - Cristina Deutsch (Revista de Istorie și Teorie Literară)
The present paper attempts, using Jean-Jacques Rousseau’s novel, Émile, as a case study, to define a series of auctorial techniques of encrypting the child symbol. This aims to examine how the idea of childhood, seen in a positive light, tries to find a place in literature, the child becoming a character with its own features, an imaginary hero upon whom various techniques can be applied to demonstrate even a philosophical – pedagogical theory such as that of Rousseau. Seen, in fact, as a conventional symbol in fiction, the child will be viewed in this case more as an incarnation of the natural child, changing, in this way, the previous perceptions of childhood, both at a scientific level and at a literary one. For Rousseau, the child is the equivalent of the good being, his evolution depending on education: a natural one in order not to be perverted by society. Rousseauʹs infant hero is essentially an orphan who will be eventually transformed into a rational adult only by the means of education coming from nature, stating that the right answers can be found only by the direct interaction with the uncorrupted environment. Therefore, for Rousseau, the child hero must be able, following his path, to construct a personal world with what is near him – a new type of persona for whom the social conventions are no longer important, but the direct experience is crucial.